Oral Literature as a Vehicle for Character Education in the Era of Cyber Society 5.0 - Siti Nur Afifatul Hikmah (MultiTech Publisher, 2023)
The era of cyber society 5.0 has influenced various fields. The era of cyber society 5.0 also affects the development of literature in education. In writing-based literature, the digitalization era does not have a significant impact on its development. Character education is a deliberate effort to help students so that they can understand, pay attention to and apply ethical values or manners in their daily lives and become better human beings. Researchers used a qualitative method with a phenomenological type. This research aims to find out 1) the form of oral literature as a medium of character education in the era of cyber society 5.0 and 2) oral literature as a vehicle for character education in the digital era. Researchers used the phenomenological paradigm of social construction with data collection techniques of participant observation, field notes, and documentation studies. While data analysis uses the Miles Huberman model, namely data collection, data reduction, data presentation, and conclusion drawing on the data found. Oral literature is expected to be a medium for character education. The values and mandates contained in oral literature become a reference in learning ethics and morals. The protection of oral literature in the digital era is something that needs to be done to prevent the loss of oral literature